TESTING READING (WORKING WITH TESTS ON READING SKILLS, ANALYZING THE RESULTS) - Eshankulova Farangiz Xayitmuratovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article focuses on test reading, providing four common test types and test objectives that differentiate between the test itself and the assessment. This article outlines the general preparation before taking the test, but each test concludes with a specific nature of the preparation and what points to assess. The value of this article is that I hope it will help teachers in testing, especially reading testing, so that they can understand what a reading test is, what to assess, how to prepare for it, and how to administer it.